Real-time performance analysis of an optimally sized hybrid renewable energy conversion unit - Erdinc, O.; Elma, O.; Uzunoglu, M.; Selamogullari, U. S. (ELSEVIER SCIENCE SA, 2014)
Lately, interest in renewable sources, especially for wind and solar energy, has gained a significant momentum with an increasing share of installed power production facilities of these sources together with the incentives of many developed/developing country governments. However, the intermittent structure of the wind and solar energy systems directly related with the dependence on meteorological conditions lowers the reliability of such sources especially for sole use in a stand-alone small scale system. Thus, utilizing these sources with energy storage units in a proper hybrid combination is the most accepted solution today to overcome the mentioned drawbacks of solar and wind systems. In order to make the mentioned hybrid system investment as economic as possible together with considering technical limitations, optimum sizing algorithms have been widely utilized. In this paper, a real-time performance analysis of an optimally sized hybrid energy system is conducted to examine the effectiveness of the optimum sizing approach proposed in a recent study of the authors. The experimental tests have been realized in Davutpasa Campus of Yildiz Technical University, Istanbul considering different case studies and worst case scenarios. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Fuel cell; Fuzzy logic; Hybrid system; Optimum sizing; Solar energy; Wind energy; FUEL-CELLS; SYSTEMS; Construction & Building Technology; Energy & Fuels; Engineering